Mapeamento e comparação de instrumentos para rastreio e estratificação da fragilidade em idosos comunitários - Andrade, Luiz Eduardo Lima de (2021)
Introduction: Frailty in the older people represents a state of physiological vulnerability related to age, produced by the reduction of homeostatic reserve and the body's ability to face a varied number of negative health outcomes. Early recognition of this syndrome is important, as it identifies older people at higher risk of unfavorable outcomes. Objective: To map valid instruments in the literature for screening and stratification of frailty community-dwelling older people, in addition to comparing them to find the best option. Methods: Article 1 - This is a scope review carried out through the search for instruments available in the literature for assessment and stratification of frailty in community-dwelling older people. The searches were carried out in 5 Medline, LILACS, Scopus, Web of Science and CINAHL databases, with the following search strategy: frail OR frailty AND “independent living” OR “community dwelling” AND aging OR elderly AND “Observational Study”. A search of the gray literature was also performed in order to identify additional relevant studies. Data were presented and analyzed descriptively. Article 2 – This is a methodological study to assess the discriminative validity of the Vulnerable Elderly Survey-13 (VES-13) and Clinical Functional Vulnerability Index-20 (IVCF-20) instruments compared to the Frailty Phenotype. It was carried out with community-dwelling older people aged 60 years and over, of both sexes, residing in Parnamirim, in the northeast region of Brazil. The frail and non-frail groups, identified through the Frailty Phenotype, were compared using the Student's t test and the effect size for each instrument score. To investigate the correlation between the three instruments, Pearson's correlation was performed. Discriminative validity was tested by analyzing the ROC curve, in addition to calculating the accuracy of the instruments. Results: Article 1 - 55 studies were selected for the final analysis of this research. Seventeen instruments were analyzed, the Fried Frailty Phenotype being the most used method, being present in 25 studies (45.5%). Regarding the assessment domains, six instruments assess only physical issues, four assess physical, psychological and social issues, and the other instruments have more than three domains for assessing frailty. Article 2 - A total of 732 elderly people were evaluated, among which 17.1% presented themselves as frail according to Fried's Frailty Phenotype. The Pearson correlation found between Frailty Phenotype and CFVI-20 was r=0.53 (p<0.001), whereas for VES13, this value was r=0.42 (p-value<0.001). The difference between the means of the frail and non-frail groups in the VES-13 and CFVI-20 scores with the Phenotype were statistically significant (p<0.001), with an effect size of 0.95 and 1.26, respectively. The instruments proved to be valid to discriminate frail from non-frail older people (p<0.001), where the CFVI-20 presented an AUC of 0.81 and the VES-13 of 0.75. Conclusions: The assessment of frailty in community-dwelling older people can be performed using different instruments. The scoping review serves as a guiding guide for professionals in the area of geriatrics, demonstrating 17 instruments applicable to the context of community-dwelling older people, pointing out advantages and disadvantages in deciding on the instrument to be used. The instruments VES-13 and CFVI-20 have good discriminative validity for assessing frailty in community-dwelling older people, being better for identifying frail than non-frail older people. When comparing these tools, the CFVI-20 proved to be better than the VES-13.